2012
DOI: 10.1002/jbm.b.32838
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of novel Ti‐24Nb‐4Zr‐7.9Sn alloy for dental implant applications in vitro

Abstract: Ti-24Nb-4Zr-7.9Sn (TNZS) alloy is a newly developed β-titanium alloy considered suitable for dental implant applications due to its low elastic modulus and high strength. The aim of this study was to investigate the corrosion behavior of TNZS alloy through a static immersion test in various simulated physiological solutions, namely, artificial saliva, lactic acid solution, fluoridated saliva, and fluoridated acidified saliva for 7 days. The corrosion behavior of commercially pure titanium and Ti-6Al-4V alloy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Previous work has recorded the immunogenic effect on the participation of the products of titanium corrosion in amplifying host inflammatory response and enhancing bone loss in peri‐implantitis lesions by means of an increased release of proinflammatory cytokines, 15 TNF‐α, 11 IL‐1β, 14 and RANKL 17 by host cells in the presence of titanium products. Nonetheless, the present work unveiled a previously unexplored association between bacterial plaque, dissolved titanium released into the peri‐implant tissues and peri‐implantitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has recorded the immunogenic effect on the participation of the products of titanium corrosion in amplifying host inflammatory response and enhancing bone loss in peri‐implantitis lesions by means of an increased release of proinflammatory cytokines, 15 TNF‐α, 11 IL‐1β, 14 and RANKL 17 by host cells in the presence of titanium products. Nonetheless, the present work unveiled a previously unexplored association between bacterial plaque, dissolved titanium released into the peri‐implant tissues and peri‐implantitis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that the specific bacterial niche associated with peri‐implant microenvironments might have a role in addition to the interaction with host immune responses that may also contribute to peri‐implantitis. In addition to bacteria, aggressive chemical stimuli, such as acidic fluoride solutions, have been associated with corrosion 10 , 11 . Furthermore, the electrical conductivity of titanium in the presence of oral bacteria has been shown to provide a closed circuit that may enhance the bio‐corrosive process 12 …”
mentioning
confidence: 99%
“…Titanium and its alloys are known for having excellent biocompatibility and corrosion resistance; however, Ti metal ion release has been previously reported in vivo and with in vitro experiments [21]. Kumazawa et al [22] reported that Ti particles can indeed induce a cytotoxic response in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many studies reporting corrosion and mechanical damage of metallic implants in vivo, including detailed Scanning Electron Micrography [9]- [12], the authors do not find any work, particularly corresponding to patients in Indian subcontinent, where metallurgical investigations are corroborated with the clinical findings on the same implants.…”
Section: Introductionmentioning
confidence: 87%